Chemical Composition of Paddy Straw as Affected by Treatment with Maize Spent Liquor - 1; 1; 1; 2 (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The experiment was conducted to study the chemical composition of untreated paddy straw and that treated with Maize spent liquor (MSL) at varying levels (10, 20 and 30 %) and incubated for one day. The DM, OM, TA, CP, EE, CF, NFE, Ca and P content of Maize spent liquor (MSL) were 16.88, 91.96, 8.04, 14.33, 4.37, 0.00, 73.26, 0.24 and 0.69%, respectively. Higher (p <0.01) CP content was observed in paddy straw treated with 30% MSL compared to untreated, while non-significant differences were observed in OM and TA contents in different treatments. Higher EE and lower CF (%) values were recorded in paddy straw treated with 30% MSL compared to untreated straw. No significant differences were observed in NDF, ADF, hemicellulose, and silica (%) contents in paddy straw treated with varying levels of MSL. However, the values were significantly lower than those of untreated straw. Cellulose and ADL (%) contents were decreased significantly (p <0.01), while calcium and phosphorus (%) improved (p <0.01) in paddy straw treated with increased levels of MSL compared to untreated straw. The study suggests a significant effect on the chemical composition of paddy straw treated with varying levels of MSL. It is concluded that MSL can be used up to 30 % for paddy straw treatment, revealing better chemical composition than untreated straw.